IMPLEMENTASI KEBIJAKAN PENGELOLAAN SAMPAH MENJADI ENERGI LISTRIK Studi Kasus : PLTSA BENOWO SURABAYA - Alden Farrel Wibawa; Supratiwi Supratiwi (Journal of Politic and Government Studies, 2026)
The problem of high waste accumulation in Surabaya has encouraged the local government to implement a technology-based waste management policy through the Benowo Waste-to-Energy Power Plant (PLTSa). This policy aims to reduce the volume of waste sent to landfills while converting waste into electrical energy. This study aims to analyze the implementation of the waste-to-energy policy at the Benowo PLTSa in Surabaya using Merilee S. Grindle’s policy implementation theory, which consists of two main dimensions: content of policy and context of implementation. The research uses a qualitative approach with a case study method. Primary data were obtained through in-depth interviews with the Surabaya Environmental Agency, PLTSa operators, WALHI East Java, local authorities, and surrounding communities, supported by field observations and document studies. The results show that administratively and technically the policy has been implemented and is able to process waste into electrical energy, with a management rate reaching 100% of the incoming waste volume (205,510 tons in 2024 and 234,021 tons in 2025). However, challenges remain in the socio-environmental aspect, particularly related to odor disturbances experienced by local communities and the limited space for public participation in the decision-making process. Therefore, the implementation of the waste-to-energy policy at the Benowo PLTSa in Surabaya has generally been carried out and has achieved its operational objectives, but it is not yet fully optimal in social and environmental aspects and still requires improvement to achieve comprehensive and sustainable policy goals.